2016
DOI: 10.1111/iwj.12640
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for periprosthetic joint infection following primary total hip or knee arthroplasty: a meta‐analysis

Abstract: To identify risk factors for periprosthetic joint infection following primary total joint arthroplasty, a systematic search was performed in Pubmed, Embase and Cochrane library databases. Pooled odds ratios (ORs) or standardised mean differences (SMDs) with 95% confidence intervals (CIs) were calculated. Patient characteristics, surgical-related factors and comorbidities, as potential risk factors, were investigated. The main factors associated with infection after total joint arthroplasty (TJA) were male gend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
149
1
14

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(187 citation statements)
references
References 47 publications
23
149
1
14
Order By: Relevance
“…Thus, before TKA, it is important to conduct a careful preoperative assessment to prevent postoperative infection. Kong et al [7] reported that age, obesity, operation time, drain usage, diabetes mellitus, urinary tract infection, and rheumatoid arthritis were risk factors for periprosthetic joint infection. Ratto et al [6] reported that careful management of glucose level, general nutrition and body weight, as well as smoking cessation, reduced infection rates.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, before TKA, it is important to conduct a careful preoperative assessment to prevent postoperative infection. Kong et al [7] reported that age, obesity, operation time, drain usage, diabetes mellitus, urinary tract infection, and rheumatoid arthritis were risk factors for periprosthetic joint infection. Ratto et al [6] reported that careful management of glucose level, general nutrition and body weight, as well as smoking cessation, reduced infection rates.…”
Section: Discussionmentioning
confidence: 99%
“…PJI requires considerable effort and resources to treat, putting the patient at increased risk of further complications, including amputation, and even mortality [1]. Among the numerous identified risk factors for PJI, obesity has been recognized as a significant factor in numerous studies [2]. The impact of obesity appears to differ between hip and knee surgery, with a BMI of 30 or greater demonstrating an odds ratio (OR) of 2.04 for total hip arthroplasty and 1.39 for total knee arthroplasty in a recent meta-analysis [2].…”
Section: Editorialmentioning
confidence: 99%
“…44 Urinalysis should be performed, and symptomatic urinary tract infections should be treated prior to surgery to decrease the possibility of implant-related infections. 45 Controversy exists regarding the need for treatment of asymptomatic bacteriuria. Recent reports on elective lower extremity joint replacements have shown no benefit in association with screening and treating asymptomatic urinary tract colonization.…”
Section: Laboratory Workupmentioning
confidence: 99%